2014
DOI: 10.1111/nph.12998
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana homeobox 12 (ATHB12), a homeodomain‐leucine zipper protein, regulates leaf growth by promoting cell expansion and endoreduplication

Abstract: SummaryArabidopsis thaliana homeobox 12 (ATHB12), a homeodomain-leucine zipper class I (HDZip I) gene, is highly expressed in leaves and stems, and induced by abiotic stresses, but its role in development remains obscure.To understand its function during plant development, we studied the effects of loss and gain of function. Expression of ATHB12 fused to the EAR-motif repression domain (SRDX) -P 35S ::ATHB12SRDX (A12SRDX) and P ATHB12 ::ATHB12SRDX -slowed both leaf and root growth, while the growth of ATHB12-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
91
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 58 publications
(106 reference statements)
3
91
0
1
Order By: Relevance
“…Small organ size in bin4 is primarily caused by suppressed cell expansion associated with defects in endoreduplication [80]. Overexpression of Arabidopsis thaliana homeobox 12 (ATHB12) resulted in increased cell size, along with elevated ploidy [81]. Our results showed that 1000 μM melatonin caused significantly 2C fraction increase in cotyledons, the first pair of true leaves, and the fifth leaves, in accordance with the decrease of higher DNA content (Figure 4A–C).…”
Section: Discussionsupporting
confidence: 62%
“…Small organ size in bin4 is primarily caused by suppressed cell expansion associated with defects in endoreduplication [80]. Overexpression of Arabidopsis thaliana homeobox 12 (ATHB12) resulted in increased cell size, along with elevated ploidy [81]. Our results showed that 1000 μM melatonin caused significantly 2C fraction increase in cotyledons, the first pair of true leaves, and the fifth leaves, in accordance with the decrease of higher DNA content (Figure 4A–C).…”
Section: Discussionsupporting
confidence: 62%
“…These miRNAs may regulate Eu-rubber accumulation via suppression of their target gene expression. Previous studies have showed that Arabidopsis thaliana homeobox 12 (ATHB12), a homeodomain-leucine zipper class I (HDZip I) gene, can regulatethe cell growth during leaf development (Hur et al, 2015). Our results indicated that the HD-ZIP expression enhanced rubber content by promoting leaf and fruit growth.…”
Section: Discussionmentioning
confidence: 99%
“…Interplay between kinases and phosphatases mediates global regulation of cellular function (Li et al, ; Trotta, Konert, Rahikainen, Aro, & Kangasjärvi, ; Zhao et al, ). The reversibility of protein phosphorylation status further aids in plasticity of molecular regulation spreading its influence over replication, transcription, cell cycle progression, splicing, and epigenetic regulation (Hur et al, ; Qi et al, ; Sun et al, ; Tunc‐Ozdemir et al, ). The precise site of phosphorylation has been the study of interest in deciphering signal transduction pathways (Nühse, Stensballe, Jensen, & Peck, ).…”
Section: Introductionmentioning
confidence: 99%